The Moderating Role of Gender in the Relationship Between Nomophobia and Social Interaction Anxiety in University Students - Bulut, Arzu; Şengül, Halil; Şengül, Halil (Taylor & Francis, 2023)
Nomophobia is defined as the fear that an individual experiences related to lack of access or useof their smartphone. Studies have reported significant differences on the effects of nomophobiabetween genders. Moreover, social interaction anxiety is a condition identified as a risk factor forfuture health problems among university students. The aim of this study is to examine the moder-ating effect of gender in the relationship between nomophobia and social interaction anxiety. Thestudy’s data were collected from 331 university students aged 19 to 42. The study tested the mod-erating effect of gender in the predictor effect of social interaction anxiety on various nomophobiasub-dimensions. Social interaction anxiety had a significant predictor effect of college students’“inability to access information”and“inability to communicate,”but this effect did not vary bygender. On the other hand, the predictor effect of social interaction anxiety on“giving up conven-ience”and“losing connectedness”did vary by gender.
Keywords: Nomophobia; Social interaction anxiety; Gender; Moderating effect; University students